Jesus was Married? “SCANDALOUS!” Field Theory in Reporting on a U.S. Religion Scandal - Perreault, Gregory (Journal of media and religion, 2024)
The scandal story reflects an essential journalistic lens to understand culture; scandals circumscribe attention to the norms, values and expectations of a culture. This study explores the nature of the scandal story through an examination of a case in U.S. journalism: the coverage of the now-disproved “Gospel of Jesus’ Wife.” This study examines the initial 2012 case of an ancient papyrus scrap alleged to prove that the historical Jesus was married, and that over a period of eight years, was disproved to a complicated backstory of cultural misogyny, academic dishonesty, and a con man. Through the lens of field theory, this study aims to explore how scandal stories help shed a light on how a culture informs a newsroom doxa.